Perceived Benefits of Micro Teaching Course to Students’ Teaching Apprenticeship (PLP) - Rahmi, Adena; Farmasari, Santi; Apgrianto, Kurniawan (Program Studi Pendidikan Bahasa Inggris, 2025)
This study analyses how student-teachers at the University of Mataram’s English Education Program view the benefits of the microteaching course to get ready for their Teaching Apprenticeship (PLP). Applying a mixed-method strategy, data were collected from 30 student-teachers through a Likert-scale questionnaire and in-depth interview with six selected participants. Findings indicate that the majority of participants (76%–93%) perceived microteaching as highly beneficial for developing practical teaching skills, building confidence, designing student engagement strategies, and fostering reflective practice. Nevertheless, only 40%–57% felt adequately prepared to handle real-world classroom challenges such as managing disruptive student behavior, addressing distractions, coping with emotional stress, and delivering extended lessons—issues largely absent in the idealized microteaching setting. These results reveal a persistent gap between the structured safety of microteaching simulations and the unpredictable dynamics of authentic school environments. The study recommends enhancing microteaching by incorporating unpredictable classroom scenarios, integrating classroom management and emotional resilience modules, using role-plays that simulate authentic student behaviors, and facilitating post-PLP reflection seminars. While microteaching remains a valuable foundational component of teacher education, these improvements could better align it with the multifaceted demands of real classroom teaching.